Pembelajaran IPA Berbasis Hands-On: Tinjauan Literatur Terhadap Pengembangan Keterampilan Proses Sains - Sahar, Adnan; Amri, Haerul; Munfarikha, Ninik; Kelana, Ardian Hangga; Islam, Rukmana Fachrul (Indo-MathEdu Intellectuals Journal, 2025)
This article presents a literature review on the effectiveness of the Hands-on Activity approach in enhancing students’ SPS. Data were obtained from 15 national and international research articles that met the inclusion criteria, namely discussing science learning based on direct activities, employing experimental methods, and providing data related to SPS development. Data analysis was conducted thematically by identifying patterns from instructional designs, SPS outcomes, and implementation contexts, with the aim of systematically reviewing the effectiveness of the Hands-on Activity approach in improving students' science process skills. The review findings consistently show that Hands-on Activity positively influences both basic SPS (such as observing, classifying, and measuring) and integrated skills (such as designing experiments and interpreting data). In addition to cognitive improvements, this approach also contributes to affective and psychomotor aspects, including learning motivation, scientific attitudes, and collaboration skills. Various forms of implementation—such as activity-based worksheets, simple laboratory tools, and digital technologies—highlight the flexibility of this method in diverse school contexts. Therefore, the Hands-on Activity approach is recommended as an effective, contextual, and adaptive teaching strategy for strengthening students’ SPS in science education